An Audience Research in Music Industry: Characteristic of The Fans of BALUM - Dwi Putra, Adityawarman; Hudrasyah, Herry (Journal of Business and Management, 2012)
Music Business is an industry that requires not only musical ability but also other skills such as management skills, performance art, negotiating skills, etc. when we combine making music with making money; we become a part of the music business. This research will discuss about a musician called Balum (www.facebook.com/Balumguitar). This year Balum wants to increase the people awareness of Balum by release his first album. In developing his music career, the first step is to know who the fan is and what the characteristic of the fans is. To simplify, the problem can be expressed as: What is the characteristic of the fans of Balum? The objective of this research is to understanding the fans of Balum in terms of lifestyle and personality. By understanding those fans, Balum expected to have through understanding of his fan-base. From this point, plan a development strategy for his musical career. This research will also may be used by fellow musician as a reference for developing their own musical career in Indonesian market. The qualitative research will conduct to depict the characteristic of the existing fans. Personality approach is used to describe the personality of Balum’s fans. Demographic property and lifestyle trends among the existing fans also used to depict the characteristic of the fans. The participant of this research is the fans of Balum itself.Keywords: Audience Research, Brand Development, Market Characteristic, Music, Music Business